(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
Reliable database of cholesterol content is limited in the diet of many countries of the world. The objective of this study was to determine the cholesterol content in raw and cooked chicken meat through an accurate, precise and validate method. The raw meat sample was collected from Department of Animal Science and Technology, Sunchon National University, South Korea. The cholesterol content was determined by gas chromatography (GC) using an internal standard (5α-cholestane) method for quantification.The method was validated with respect to specificity, chromatographic parameters, linearity, precision, accuracy and limits of detection. Standards Reference Material (SRM) sample, frozen diet composition 1544 was analyzed and the results indicated that the method was accurate with over 97% recovery. The coefficient of variation of repeatability 5.2% and reproducibility 2.4% were also indicated that the method was precise. The cholesterol contents were determined in thigh and breast meat with the values of 95.54 and 71.43 mg/100g, respectively. On the other hand, cholesterol content found in cooked chicken meat with the values of 64.36 mg/100g for boiled chicken soup with ginseng and 79.40 mg/100g for chicken skewer. The present findings suggest that the method was reliable for quantification of large number cholesterol value in food samples. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (3), 533-538